2002
DOI: 10.1021/jp014416q
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomorphic Crystal Growth of the Model Steroid Methyl Analogue of Norethindrone

Abstract: Various morphologies of two polymorphs of a steroid are observed and correlated to calculated morphologies using the connected net theory. In a previous publication on our model compound, we reported polymorphic epitaxial growth as a result of variations in the supersaturation. Two additional and also unusual types of growth behavior are described in this work: the observation of crystals that have a morphology that does not correspond to its observed polymorph, also called pseudomorphism, and the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…1a) rings revealed that atoms C(11), C(9), C(16) and C(15) are, respectively, the most deviating ones from perfect planar rings. The highest deviations from the leastsquares plane passing through those rings are 0.309 (4) A for C(11), À0.256 (3) A for C(9), 0.255(3) A for C(16) and À0.314(2) A for C (15). The root mean square errors (rmse) of contributing atoms, for each ring displayed in Fig.…”
Section: Refinementmentioning
confidence: 98%
See 1 more Smart Citation
“…1a) rings revealed that atoms C(11), C(9), C(16) and C(15) are, respectively, the most deviating ones from perfect planar rings. The highest deviations from the leastsquares plane passing through those rings are 0.309 (4) A for C(11), À0.256 (3) A for C(9), 0.255(3) A for C(16) and À0.314(2) A for C (15). The root mean square errors (rmse) of contributing atoms, for each ring displayed in Fig.…”
Section: Refinementmentioning
confidence: 98%
“…1a). 4 The isomer is formed when tibolone is exposed to high temperatures and/or acidic conditions. The potential for significant degradation of tibolone to isotibolone makes it difficult to formulate and provide a pharmaceutical composition with acceptable life-time storage for a marketed product.…”
Section: Introductionmentioning
confidence: 99%
“…We only consider PBCs that are restricted to the observed slice thickness d 040 . Using the crystal graph (network of bonds) and bond energies determined by Boerrigter et al [39], we come to four PBC directions for each layer X and Y: Interesting is the fact that, although the [1 0 1] steps are the fastest propagating ones, they are always straight. This indicates that the kink density is lower, i.e.…”
Section: Step Orientations and Pbc Directionsmentioning
confidence: 99%
“…The isomer is formed at high-temperature exposure and/or acidic conditions. The isomerization mechanism involves the rearrangement on the A-ring of the double bound from carbon atoms 5 -10 to 4 -5 [3].…”
Section: Introductionmentioning
confidence: 99%